An Irish parade in Victoria Street, London - Kilkenny Association, KILK
Colour photograph showing an Irish parade in Victoria Street. A group with scarves and rosettes walk behind two men holding up the Kilkenny Association banner. The banners of the Laois and Leitrim Associations and black-and-tan flags can be seen behind them. Mounted in a card folder. Photographer unknown.